ANTONIJE ISAKOVIĆ’S PROSE IN THE TEACHING CONTEXT (Heritage, 2023)
The focus of the research was the prose of Antonije Isaković in the context of teaching literature and language. Since the sixties of the 20th century, the stories from Isaković’s first prose book Velika deca (1953) have been covered in classes, while Isaković’s prose is not represented in current plans and programs. In elementary schools, the stories „Kašika“ and „Crveni šal“ were interpreted, while in secondary schools and gymnasiums was covered the prose collection Velika deca or a selection from it. The paper examined the status of Isaković’s prose in the teaching context, based primarily on reading books from that period. Моreover, the research was an occasion for the analysis of the didactic-methodical and other apparatus of reading book as a basic textbook for the teaching of literature.
Keywords: Antonije Isaković (1923–2002), Velika deca, methodology, teaching, reading book, Serbian language, Serbian language and literature